Supporting small and medium-sized enterprises in the educational technology sector to become more research-minded: Introduction to a small collection. (16th February 2021) - Clark-Wilson, Alison; Moeini, Anissa; Anand, Kusha; Blake, Canan; Cukurova, Mutlu; De Ossorno Garcia, Santiago; Issroff, Kim; Luckin, Rose; Olatunj, Tunde; Outhwaite, Laura; Weatherby, Kristen
Abstract : page_5 other The EDUCAtional Technology Exchange programme (EDUCATE) at UCL Institute of Education provides the context for this paper, which describes the programme's vision, objectives and key activities, and sets the context for the collection of articles that follow. This university-led programme was underpinned by Luckin's (2016) golden triangle of evidence-informed educational technology (edtech) as it sought to support 252 small and medium-sized enterprises to become more research-informed through a six-month research training and mentoring programme. The evaluation of the programme's design-based research cycles revealed the importance of the careful choice and evolution of its boundary objects. These boundary objects, namely each enterprise's 'logic model' and research proposal, facilitated meaningful conversations between the programme's research mentors and the enterprises. These boundary objects involved several iterations, during which the language of the two communities became more aligned, helping to bridge the academic knowledge and practices with those of the enterprises.